Controlling physical characteristics of DNA and DNA-CTMA thin films by embedding with graphene oxide and riboflavin. (1st July 2021) - Kokkiligadda, Samanth; Dugasani, Sreekantha Reddy; Komarala, Eswaravara Prasadarao; Jeon, Sohee; Jeong, Jun-Ho; Park, Sung Ha
Abstract: DNA complexes formed with graphene oxide (GO) and riboflavin (RF) have multiple interesting characteristics and unique features owing to specific properties of the DNA. Herein, we develop a fabrication method for GO- and RF-embedded DNA and cetyltrimethyl ammonium chloride-modified DNA (DNA-CTMA) thin films with varying concentrations of GO ([GO]) and fixed [RF] content that uses a simple drop-casting process. The properties of the fabricated thin films were investigated to understand (a) the chemical interactions between GO, RF and DNA (DNA-CTMA) molecules using Fourier transform infrared (FTIR) and Raman, (b) the variation in chemical features and spin states using x-ray photoelectron spectroscopy (XPS), (c) the characteristic wavelengths using UV–Vis absorption, (d) electron transfer between energy states using photoluminescence (PL), and (e) electrical conduction using current measurements. The FTIR, Raman, XPS, and UV–Vis spectra of the GO- and RF-embedded DNA and DNA-CTMA thin films exhibit noticeable changes in peak intensity and experience peak shifts with varying [GO] content. The PL spectra of the thin films show a quenching phenomenon with increasing [GO] content due to decreases in recombination efficiency. The increases in current observed with the addition of GO to the DNA and DNA-CTMA thin films can be attributed to the conducting nature of GO. The optical and electrical properties of the GO- and RF-embedded DNA and DNA-CTMA thin films can easily be tuned by the adjusting the [GO] content. Consequently, our thin films show great promise for application in various types of bio-sensors and bio-photonic devices.